2020
DOI: 10.1200/jco.2020.38.29_suppl.240
|View full text |Cite
|
Sign up to set email alerts
|

Using an integrated social-behavioral text message approach to improve screening mammography in African American women.

Abstract: 240 Background: The rate of breast cancer among Black and White women is nearly equivalent but the death rate is 40% higher for Blacks. This disparity is often attributed to lower screening mammography rates in Black women. The effectiveness of text messages on increasing screening mammography among Black women is not well known. Importantly, the themes that are most effective at promoting behavioral changes in Black women’s breast cancer screening practices through text message interventions have not been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with other text messaging studies for preventive health activities . We did not find an increase in obtaining a mammogram from text messaging among Black women, which is surprising as qualitative studies have shown acceptability and potential in the use of text messaging in this population …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are consistent with other text messaging studies for preventive health activities . We did not find an increase in obtaining a mammogram from text messaging among Black women, which is surprising as qualitative studies have shown acceptability and potential in the use of text messaging in this population …”
Section: Discussionsupporting
confidence: 90%
“…21,[27][28][29][30] We did not find an increase in obtaining a mammogram from text messaging among Black women, which is surprising as qualitative studies have shown acceptability and potential in the use of text messaging in this population. 31,32 In trial B, there was a 1.1-percentage point higher response to the clinician endorsement letter that was not statistically significant. There are a few reasons that might explain this finding.…”
Section: Discussionmentioning
confidence: 92%